Laser versus Anti-VEGF: A Paradigm Shift for Treatment-Warranted Retinopathy of Prematurity - Hartnett, M. Elizabeth; Stahl, Andreas (Ophthalmology and therapy, 2023)
Retinopathy of prematurity (ROP), a leading cause of childhood blindness, has historically been associated with blindness from overgrowth of blood vessels from the retina into the vitreous that lead to complex retinal detachments. Our understanding of ROP has evolved with the survival of extremely low-birthweight infants and includes not only overgrowth of blood vessels, but also insufficient developmental retinal vascular growth in early phases of the disease. Our current treatments of ROP have focused on methods to improve perinatal and prenatal care, reduce premature birth, and prevent early phases of ROP. Nonetheless, addressing vasoproliferation in treatment-warranted eyes remains the mainstay of management. Two main treatment strategies co-exist today: laser treatment, which has been the standard of care since the 1990s, and anti-VEGF injections, which have been used since early reports in 2007 (Travassos et al. in Ophthalmic Surg Lasers Imaging, 38:233–237, https://doi.org/10.3928/15428877-20070501-09 , 2007, Shah et al. in Indian J Ophthalmol 55:75–76, https://doi.org/10.4103/0301-4738.29505 , 2007, Quiroz-Mercado et al. in Semin Ophthalmol 22:109–125, https://doi.org/10.1080/08820530701420082 , 2007).